1993
DOI: 10.1007/bf00297542
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugates with Neu5Ac(?2,6)Gal(?1,4)GlcNAc sequences: a selective lectin-histochemical property of Kurloff cells in guinea pig thymus

Abstract: The Kurloff cell (KC), a natural killer lymphocyte, contains a large (10-microns diameter) periodic acid-Schiff (PAS)-positive lysosome-like inclusion body called the Kurloff body (KB), which exhibits strong acid phosphatase activity. The presence of Sambucus nigra agglutinin (SNA)-reactive Neu5Ac(alpha 2,6)-D-Gal/Gal-NAc(beta 1,4)GlcNAc oligosaccharide sequences and the absence of the corresponding Neu5Ac(alpha 2,3) Maackia amurensis agglutinin (MAA)-reactive sequence in the major 35-kDa N-glycosylproteins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…To ascertain the presence of polysialosyl units, we tested the effect of endo N; after pretreatment of peak IV with endosialidase, anti-Men B antibody did not give any positive reaction (fig 6b). KC major glycoproteins, previously characterized as containing SNAreactive oligosaccharides (fig 6c) with ~t(2,6)-linked sialic acid [33,42] were used as negative control glycoproteins for anti- Men B (fig 6d). Crude tissue extracts from fetal mouse brain and immunopurified embryonic forms of N-CAM were used as positive control for the presence of (NeuAc~2,8) n sequences (fig 6e, f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ascertain the presence of polysialosyl units, we tested the effect of endo N; after pretreatment of peak IV with endosialidase, anti-Men B antibody did not give any positive reaction (fig 6b). KC major glycoproteins, previously characterized as containing SNAreactive oligosaccharides (fig 6c) with ~t(2,6)-linked sialic acid [33,42] were used as negative control glycoproteins for anti- Men B (fig 6d). Crude tissue extracts from fetal mouse brain and immunopurified embryonic forms of N-CAM were used as positive control for the presence of (NeuAc~2,8) n sequences (fig 6e, f).…”
Section: Resultsmentioning
confidence: 99%
“…Using highly purified KC [29], soluble extracts obtained after dissociative extraction in either 4 M GnHCI or 7 M urea were subjected to ion exchange chromatography and the macromolecules responsible for these histochemical affinities were identified: i) unbound major 30-35 kDa glycoproteins designated as major KC GP [30,35] among which a fraction containing Neu5Ac(oc2,6)-D-Gal/Gal-NAc(~I,4)GIcNAc oligosaccharide sequences were shown to correspond to acid phosphatase subunits [33,42]; and it) protease-resistant chondroitin-4-sulphate proteoglycans eluted at 0.55 M NaCI [31,36] which correspond to PASpositivity and TB-metachromasia of the KB, respectively.…”
mentioning
confidence: 99%
“…In H35 rat hepatoma cells, dexamethasone increased a2.6-ST expression (45,46). Furthermore, Oulhaj et al (47) found that the natural killer T-cells in thymus of estrogenized or pregnant guinea pigs stained with SNA. In the present study, the decidual cells of human and rat mature placenta stained vividly with antia2,6-ST.…”
Section: Discussionmentioning
confidence: 99%
“…It would be a good idea in another topical issue to cover the application of other modern techniques to the thymus. These might include confocal microscopy, which is seldom used in this area, and lectin histochemistry, as we have done in our study on Kurloff cells at the corticomedullary junction of the thymus in the guinea-pigs (Oulhaj et al, 1993).…”
Section: Introduction To the Thymusmentioning
confidence: 99%